An assessment of agents of hepatotoxicity and neurotoxicity - Wijamunige, Buddhika Chameera (2019)
In recent years there is growing concern about the neurotoxicity of alcohol, acetaldehyde, H2O2 and organophosphate pesticides on neuronal cells. An assessment of the neurotoxicity of these four commonly encountered neuro-toxicants was conducted using a human neuroblastoma SH-SY5Y cell line. Cells were cultured at four different media concentrations: Culture media without (0%) foetal bovine serum (FBS), 3% FBS, 10% FBS, 15% FBS and with EMEM. Passage 12-14 SH-SY5Y cells were seeded in 96 well plates and challenged with neuro-toxicants prepared at serial dilutions in respective growth media. Cell viability was assessed using a (3- [4, 5-dimethylthiazol -2-yl] 2-5 diphenyl tetrazolium bromide) (MTT) assay. Ethanol, Acetaldehyde, H2O2, and the pesticides Azamethiphos-oxon, and Chlorpyrifos-oxon reduced SH-SY5Y cell viability in a dose-dependent manner. Cells grown in low serum media showed higher cell cytotoxicity to all neurotoxic chemicals, suggesting serum proteins may limit release or action of the toxic moieties of test compounds. Western blot analysis was performed using cell lysates of SH-SY5Y cells treated with 50, 100, and 200 mM ethanol to examine tubulin protein expression after 24-hour exposure. There were no significant changes in tubulin protein levels in ethanol exposed cells over the range of used concentration for 24 hours. Collectively, the results obtained determined concentrations of the neuro-toxicants that inhibited cell viability by 50% (IC50s), and these will provide an insight to the health effects associated with moderate to high neuro-toxicant exposures in humans.